PRINCIPALS’ KNOWLEDGE AND EXPERIENCES IN EXECUTING INSTRUCTIONAL ROLES IN SCHOOLS - Dr.Saltiel Khololo Collen Mataboge; Prof.Vimbi Petrus Mahlangu (RADJA PUBLIKA, 2023)
This article sought to examine the ways in which secondary school principals support School Management Teams (SMTs) in carrying out their duties as instructional leaders. How can principals empower the SMTs is the main thesis of this article. The emphasis will be on principals' experiences carrying out their instructional leadership responsibilities in the South African province of Gauteng's Tshwane-West District. The thesis of this essay is that when principals fail to fulfill their obligations to support the school administration, student performance does not increase. Therefore, it becomes an issue if the administrator is not held responsible for raising student and teacher performance levels in the classroom. Design, method, and strategy A questionnaire was used to obtain the data. Through a thorough application of the knowledge gathered from the literature study, the questionnaire's content was made to hold up. To validate the questionnaire, a pilot study was done. The triangulation of data from many sources, including focus-group interviews and the questionnaire, served as the primary method of reliability in this study. Principals of secondary schools in South Africa's Gauteng province's Tshwane-West District made up the study's sample. All 55 secondary schools located in the Tshwane West District were included in the study using the total sample methodology.